Video SAVASIK sebagai Media yang Efektif untuk Menumbuhkan Minat Wanita Usia Subur untuk Mengikuti Pemeriksaan IVA - Rahayu, Yunita Diah; Sumasto, Hery; Purwanto, Triana Septianti; Usnawati, Nana (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2025)
Women's reproductive health problems have a broad impact and affect various aspects of life. Based on data from the Visual Inspection with Acetic Acid (IVA) Program of Ngujung Health Center, in 2021 Ngujung Health Center had five women suspected of having cervical cancer, and was ranked 7th out of 22 health centers in Magetan Regency with a figure of 0.2%. The purpose of this study was to determine the effectiveness of educational media in the form of SAVASIK videos in fostering the interest of women of childbearing age to undergo IVA examinations in the Ngujung Health Center area. This study was an analytical study with a pretest-posttest with control group design. The subjects of this study were 96 women of childbearing age in the Ngujung Health Center area, Magetan, who were selected using the cluster sampling technique. The subjects were divided into a treatment group that received education with the SAVASIK video as a medium and the rest were a control group that was given education using leaflets, each consisting of 48 women of childbearing age. In the pre- and post-intervention phases, the interests of women of childbearing age were measured by filling out a questionnaire. Furthermore, a comparative analysis of interest between the two groups was conducted using the McNemar test. The results of the analysis in this study obtained a p value <0.001, which means that there was a difference in the interest of women of childbearing age to undergo IVA examination between the group that received education using the SAVASIK video and leaflets, with higher achievement in the treatment group. Thus, it could be concluded that the SAVASIK video is effective in increasing the interest of women of childbearing age to undergo IVA examination. The SAVASIK video is expected to be used as an innovation by the Ngujung Health Center as a means of health promotion.Keywords: women of childbearing age; visual inspection of acetic acid (IVA), educational video; interest ABSTRAK Permasalahan kesehatan reproduksi perempuan mempunyai dampak yang luas dan mempengaruhi berbagai aspek kehidupan. Berdasarkan data Program pemeriksaan inspeksi visual asam asetat (IVA) Puskesmas Ngujung, pada tahun 2021 Puskesmas Ngujung mempunyai lima orang wanita suspek kanker serviks, dan menduduki peringkat ke 7 dari 22 puskesmas di Kabupaten Magetan dengan angka 0,2%. Tujuan penelitian ini adalah untuk mengetahui efektivitas media edukasi berupa video SAVASIK dalam menumbuhkan minat wanita usia subur untuk menjalani pemeriksaan IVA di wilayah Puskesmas Ngujung. Penelitian ini merupakan studi analitik dengan rancangan pretest-posttest with control group. Subyek penelitian ini adalah 96 wanita usia subur di wilayah Puskesmas Ngujung, Magetan yang dipilih dengan teknik cluster sampling. Subyek dibagi menjadi kelompok perlakuan yang mendapatkan edukasi dengan video SAVASIK sebagai media dan selebihnya adalah kelompok kontrol yang diberi edukasi menggunakan leaflet, yang masing-masing terdiri atas 48 wanita usia subur. Pada fase sebelum dan sesudah intervensi pada kedua kelompok dilakukan pengukuran minat wanita usia subur melalui pengisian kuesioner. Selanjutnya dilakukan analisis perbandingan minat di antara kedua kelompok, menggunakan uji McNemar. Hasil analisis pada penelitian ini mendapatkan nilai p <0,001 yang berarti bahwa ada perbedaan minat wanita usia subur untuk menjalani pemeriksaan IVA antara kelompok yang mendapatkan edukasi menggunakan video SAVASIK dan leaflet, dengan pencapaian lebih tinggi pada kelompok perlakuan. Dengan demikian bisa disimpulkan bahwa video SAVASIK efektif untuk meningkatkan minat wanita usia subur guna menjalani pemeriksaan IVA. Video SAVASIK diharapkan dapat dijadikan sebagai inovasi Puskesmas Ngujung sebagai sarana promosi kesehatan.Kata kunci: wanita usia subur; inspeksi visual asam asetat (IVA), video edukasi; minat